Brief Report: Rebound HIV Viremia With Meningoencephalitis After Antiretroviral Therapy Interruption After Allogeneic Bone Marrow Transplant. (1st March 2022) - Capoferri, Adam A.; Redd, Andrew D.; Gocke, Christopher D.; Clark, Laura R.; Quinn, Thomas C.; Ambinder, Richard F.; Durand, Christine M.
Abstract : Background: Allogeneic bone marrow transplant (alloBMT) in people living with HIV can lead to the undetectable levels of HIV reservoirs in blood, even using highly sensitive assays. However, with antiretroviral therapy (ART) interruption, rebound of HIV viremia occurs. The source of this rebound viremia is of interest in HIV cure strategies. Methods: Within a trial of alloBMT in individuals with hematologic malignancies and HIV (ClinicalTrials.gov, NCT01836068), one recipient self-interrupted ART after achieving >99.5% host cell replacement in peripheral blood by day 147 and developed severe acute retroviral syndrome with meningoencephalitis at 156 days post alloBMT. We isolated replication-competent HIV using a quantitative viral outgrowth assay at 100 and 25 days before alloBMT and from the same time points before alloBMT for HIV DNA and cell-associated RNA from peripheral blood mononuclear cells and resting memory CD4 + T cells. We isolated HIV RNA in plasma and cerebrospinal fluid (CSF) at viral rebound. We sequenced the RT-region of pol and performed neighbor-joining phylogenetic reconstruction. Results: Phylogenetic analysis revealed an identical viral sequence at both pre-alloBMT time points accounting for 9 of 34 sequences (26%) of the sampled HIV reservoir. This sequence population grouped with viral rebound sequences from plasma and CSF with high sequence homology. Discussion: Despite >99.5% replacement of host cells in peripheral blood, ART interruption led to HIV viral rebound in plasma and CSF. Furthermore, the rebound virus matched replication-competent virus from resting memory CD4 + T cells before alloBMT. This case underscores that HIV-infected recipient cells can persist after alloBMT and that latent replication-competent virus can reestablish infection.